2013
DOI: 10.1007/s00056-013-0145-0
|View full text |Cite
|
Sign up to set email alerts
|

Stand der Pubertätsentwicklung bei Kindern und Jugendlichen während der kieferorthopädischen Therapie

Abstract: Boys and girls in Germany undergo orthodontic treatment at the same age. Given the delayed onset of puberty in boys, most are still pre-pubertal, whereas most girls have reached an advanced stage of puberty by the time they undergo treatment--a discrepancy that could have therapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Growth references also showed a connection between increase in height and earlier timing of pubertal growth spurt (30). Our findings may be partly explained by differences in pubertal status while undergoing orthodontic treatment (31). It has also been shown that tooth eruption in females is more advanced compared to males (32).…”
Section: Mesiopalatal Rotation Of Upper First Molars Has Been Reportesupporting
confidence: 63%
“…Growth references also showed a connection between increase in height and earlier timing of pubertal growth spurt (30). Our findings may be partly explained by differences in pubertal status while undergoing orthodontic treatment (31). It has also been shown that tooth eruption in females is more advanced compared to males (32).…”
Section: Mesiopalatal Rotation Of Upper First Molars Has Been Reportesupporting
confidence: 63%
“…When the treatment effect was compared between the genders, a larger effect was seen in boys. One possible explanation for this could be that boys and girls were in a different maturation phase [ 18 ]. When maximal space gain is the goal of the headgear treatment, early onset of treatment could be beneficial, especially before eruption of the second molars.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was recently found that irrespective of gender, most subjects undergoing orthodontic treatment in Germany were 12-13 years old [21]. At this age, 60% of the girls and only 38% of the boys had already attained advanced stages of pubertal development.…”
Section: Discussionmentioning
confidence: 99%